Ebstein anomaly, left ventricular non‐compaction, and early onset heart failure associated with a de novo α‐tropomyosin gene mutation. Issue 8 (13th May 2016) - Kelle, Angela M.; Bentley, S. Jared; Rohena, Luis O.; Cabalka, Allison K.; Olson, Timothy M.
Abstract : Ebstein anomaly of the tricuspid valve (EA) can be associated with left ventricular non‐compaction (LVNC), a rare congenital cardiomyopathy. We report a 2 year‐old female with EA and severe tricuspid regurgitation, LVNC, pulmonary hypertension, and chronic biventricular systolic heart failure, who died during evaluation for cardiac transplantation. Gene panel testing revealed a heterozygous de novo missense mutation in TPM1, which encodes the cardiac sarcomeric thin filament protein α‐tropomyosin. The c.475G>A variant results in a p.Asp159Asn substitution, altering a highly conserved residue predicted to be damaging to protein structure and function. TPM1 is the second gene linked to EA with LVNC in humans, implicating overlap in the molecular basis of structural and myopathic heart disease. © 2016 Wiley Periodicals, Inc.